A prospective observational study of trial of labor after cesarean in rural India. Issue 2 (7th January 2015) - Soni, Anjali; Sharma, Chanderdeep; Verma, Suresh; Justa, Usha; Soni, Pawan K.; Verma, Ashok
Abstract: Objective: To determine the success rate of trial of labor after cesarean (TOLAC) in rural India. Methods: The present prospective observational study enrolled pregnant women attending Dr Rajendra Prasad Government Medical College, Kangra, India, in 2013. Eligible women had a previous low‐segment cesarean delivery and had a singleton pregnancy with cephalic presentation. Women in labor were managed as per the institutional protocol. Results: In total, 482 women were included. TOLAC led to a vaginal delivery in 383 (79.6%) women. Overall, 2 (0.4%) women had scar rupture, and 4 (0.8%) had scar dehiscence. Fetal death was recorded in one woman with scar rupture, for whom peripartum hysterectomy was necessary. Blood loss was significantly lower among the 316 women with normal vaginal delivery than among the 99 who underwent cesarean ( P < 0.001). Blood transfusion was required in 2 (0.6%) women with normal vaginal delivery and 2 (2.0%) with cesarean delivery ( P = 0.05). The proportion of neonates who had to be admitted to intensive care did not differ significantly by mode of delivery ( P = 0.06). Conclusion: Under strict supervision, TOLAC is a reasonable option even in rural India.